Progress on Ongoing Waste form HIP projects at ANSTO. (2nd April 2018) - Vance, Eric R.; Chavara, Dorji T.; Gregg, Daniel J.
Abstract: Since the year 2000, Synroc has evolved from the titanate full-ceramic waste forms developed in the late 1970s to a hot isostatic pressing (HIP) technology platform that can be applied to produce glass, glass–ceramic, and ceramic waste forms and where there are distinct advantages over vitrification in terms of, for example, waste loading and suppressing volatile losses. This paper describes recent progress on waste form development for intermediate-level wastes from 99 Mo production at ANSTO, spent nuclear fuel, fluoride pyroprocessing wastes and 129 I. The microstructures and aqueous dissolution results are presented where applicable. This paper provides perspective on Synroc waste forms and recent process technology development in the nuclear waste management industry.